2017
DOI: 10.1016/j.cell.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Project DRIVE: A Compendium of Cancer Dependencies and Synthetic Lethal Relationships Uncovered by Large-Scale, Deep RNAi Screening

Abstract: Elucidation of the mutational landscape of human cancer has progressed rapidly and been accompanied by the development of therapeutics targeting mutant oncogenes. However, a comprehensive mapping of cancer dependencies has lagged behind and the discovery of therapeutic targets for counteracting tumor suppressor gene loss is needed. To identify vulnerabilities relevant to specific cancer subtypes, we conducted a large-scale RNAi screen in which viability effects of mRNA knockdown were assessed for 7,837 genes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
610
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(663 citation statements)
references
References 56 publications
34
610
0
Order By: Relevance
“…organoids, mice), human cancer cell lines will for a long time remain the most readily accessible options for understanding the molecular basis of oncogenesis. Cell lines have notably proven to be useful for testing drug efficacy [10] and identifying synthetic lethality [12]. Therefore, a thorough characterization of the shared molecular signatures between HCC cell lines and the counterpart primary tumours is highly needed for defining core and novel alterations that can be investigated in vitro with the highest prospect of clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…organoids, mice), human cancer cell lines will for a long time remain the most readily accessible options for understanding the molecular basis of oncogenesis. Cell lines have notably proven to be useful for testing drug efficacy [10] and identifying synthetic lethality [12]. Therefore, a thorough characterization of the shared molecular signatures between HCC cell lines and the counterpart primary tumours is highly needed for defining core and novel alterations that can be investigated in vitro with the highest prospect of clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…We retrieved cancer dependency and synthetic lethal relationship data from Project Drive 46 and calculated the dependency of EZH2, SUZ12 and EED in three different breast cancer cell lines, MDA-MB-453 (MLL3-PHD domain mutation), MDA-MB-463 (MLL3-WT) and T47D (MLL3-Non-PHD domain mutation). Cells with MLL3-PHD domain mutation are more sensitive to the depletion of all the three PRC2 components compared to MLL3-WT and –non PHD domain mutation cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmid and sample raw counts of sgRNA for cell lines from Project DRIVE 46 were downloaded and analyzed using an in-house script. The plasmid and sample raw counts per shRNA were normalized in pairs using Trimmed Mean of M-values (TMM) normalization.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have observed that cancer cell lines exhibit highly variable genetic dependencies for cellular fitness (Bertomeu et al, 2018; Blomen et al, 2015; Hart et al, 2015; Hart et al, 2017a; McDonald et al, 2017; Meyers et al, 2017; Tsherniak et al, 2017; Wang et al, 2015; Wang et al, 2017b) in a manner that reflects the diverse genomic and transcriptomic alterations a cell may accumulate during tumorigenesis. Project Achilles (Broad Institute of MIT and Harvard) seeks to systematically map genetic vulnerabilities across large collections of cancer cell lines, including the Cancer Cell Line Encyclopedia (CCLE) (Barretina et al, 2012), and has recently performed genome-scale perturbation screens in 501 cancer cell lines using RNA interference (RNAi) (Tsherniak et al, 2017) and in 342 cancer cell lines using CRISPR-Cas9 (Meyers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%